Bibliometric Analysis of the Creator Economy - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
The creator economy has emerged as a rapidly developing research domain driven by the expansion of digital platforms, content monetization models, and creator-centered economic ecosystems. Despite increasing academic attention, the intellectual structure, thematic evolution, and global collaboration patterns of creator economy research remain fragmented and insufficiently synthesized. This study aims to map the development of creator economy research and identify major trends, influential contributors, emerging themes, and future research directions through a bibliometric approach. The study employs bibliometric analysis using publications indexed in the Scopus database and visualized through VOSviewer. Several analytical dimensions were examined, including co-authorship networks, institutional collaboration, country collaboration, citation analysis, keyword co-occurrence, overlay visualization, and density visualization. The findings reveal that creator economy research has developed into an interdisciplinary field connecting economics, digital platforms, social media, information systems, innovation, and emerging technologies. Co-authorship and institutional analyses indicate that scientific production remains concentrated among several influential scholars and institutions, while country collaboration analysis identifies the United States, China, India, and the United Kingdom as leading contributors to the field. Keyword analysis demonstrates a thematic transition from foundational discussions on economics, employment, and commerce toward more specialized topics including social media ecosystems, creator monetization, artificial intelligence, blockchain, decentralization, sustainability, and intellectual property.